Papel del endotelio en hipertensión inducida por el embarazo: ¿alteraciones comunes a las de la aterosclerosis? - López-Jaramillo, Patricio (2014)
Pregnancy induced hypertension, called preeclampsia (PE) when accompanied by proteinuria, is an alteration that occurs in the second trimester of pregnancy and is characterized by presence of hypertension and proteinuria. Adaptative physiologic changes occur during normal pregnancy including insulin-resistance (IR), hyperlipidemia, hypercoagulability, inflammation, and hyperdynamic circulatory status. Expression of these changes is exaggerated in women developing PE. These alterations are also present in the metabolic syndrome (MS) risk factors cluster, which is in turn a risk factor for developing type 2 diabetes mellitus (DM2) and cardiovascular disease (CVD). In this review endothelial dysfunction is proposed as a common alteration that explains the presence of these two common diseases in Latin America.